Coniston $1 (BVolume 03s - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"Coniston $1 (BVolume 03" by Winston Churchill is a novel published in 1906. Set against the backdrop of New Hampshire politics, this bestselling work follows the story of Jethro Bass, a political boss character based on real politician Ruel Durkee. The novel drew such vivid parallels to actual places and figures that contemporary readers recognized real New Hampshire locations in its pages, while former Senator William E. Chandler felt compelled to publicly defend Durkee's reputation against the book's unflattering portrayal. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Coniston_(novel)
Release date is 2004-10-17
Produced by Pat Castevans and David Widger
Keywords: New England -- Fiction; New England -- Politics and government -- Fiction